2008
DOI: 10.14232/jengeo-2008-43853
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and biological aspects of human impacts on urban soils of Szeged (SE Hungary)

Abstract: Urban soils have generally suffered significant alteration both regarding their physical, chemical, as well as biological properties. Soil samples were taken at 25 sites from horizons of soil profiles located in the downtown and surroundings of Szeged in order to examine diagnostic properties different from natural soils (artefacts, humus content, quality of organic matter, pH (H2O, KCl), carbonate content, nitrogen content). Furthermore, topsoils were taken nearby 9 profiles to survey some basic biological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The effect of vegetation cover -if present-on the oribatid mite community remains unclear (Osler et al, 2006), but might affect soil microclimate and thickness of the litter layer. Photosynthetically active radiation reaching the soil surface -PARss-(% incident light at soil surface/light above vegetation) was measured as a proxy for the total vegetation cover yielding favourable or unfavourable conditions for oribatid mites depending on their moisture preference and soil vertical distribution (Puskás et al, 2008). PARss was estimated as the proportion between the incident PAR and PAR at soil surface (Netto et al, 2015) based on 80 measurements per site using a PAR ceptometer AccuPar .…”
Section: Environmental Variablesmentioning
confidence: 99%
“…The effect of vegetation cover -if present-on the oribatid mite community remains unclear (Osler et al, 2006), but might affect soil microclimate and thickness of the litter layer. Photosynthetically active radiation reaching the soil surface -PARss-(% incident light at soil surface/light above vegetation) was measured as a proxy for the total vegetation cover yielding favourable or unfavourable conditions for oribatid mites depending on their moisture preference and soil vertical distribution (Puskás et al, 2008). PARss was estimated as the proportion between the incident PAR and PAR at soil surface (Netto et al, 2015) based on 80 measurements per site using a PAR ceptometer AccuPar .…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Nonetheless, the physical and chemical properties of urban soils (from the Latin word for city, 'urbs') often differ significantly from natural soils due to, e.g., construction activities that cause mechanical disturbances, and more frequent occurrences of unnatural components such as construction residues and contaminants from industries, domestic heating, heavy traffic and waste disposal (Lehmann and Stahr, 2007;Mamehpour et al, 2021;Puskás et al, 2008;Rezapour et al, 2022). It has repeatedly been shown that urban soils contain elevated concentrations of heavy metals (Bretzel and Calderisi, 2006;Clarke et al, 2015;Mitchell et al, 2014;Szolnoki et al, 2013), and as these elements are non-degradable they constitute a persistent challenge to produce safety.…”
Section: Introductionmentioning
confidence: 99%